2019 13th International Symposium on Medical Information and Communication Technology (ISMICT) 2019
DOI: 10.1109/ismict.2019.8743894
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Antenna-Body Distance on the WBAN Channel Characteristics

Abstract: This paper presents a simulation based study on the impact of the antenna-body distance on the ultra wideband (uwb) on-body radio channel characteristics. The antenna used in this study is a recently published highly directional cavitybacked uwb antenna, designed for inbody communications, e.g. capsule endoscope localization. The on-body channel characteristics are evaluated both in frequency and time domains with several antenna-body distances as well as with several antenna location options. Furthermore, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

5
4

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…For these on-body antennas, the optimal antenna matching is obtained with antenna-body distance 30 mm, which however is not considerable for practical applications. Besides, in [16] it was found that although the antenna matching is weaker with antennabody distance 4 mm, there are not significant differences in the propagation depths between the antenna-body distances 30 mm and 4 mm. For the Ring antenna, within the frequency range of interest, i.e., 3.75 -4.25 GHz, path loss is smallest, approximately 60 dB, as the capsule is located on the middle of SI.…”
Section: A On-body Antenna Locationmentioning
confidence: 93%
“…For these on-body antennas, the optimal antenna matching is obtained with antenna-body distance 30 mm, which however is not considerable for practical applications. Besides, in [16] it was found that although the antenna matching is weaker with antennabody distance 4 mm, there are not significant differences in the propagation depths between the antenna-body distances 30 mm and 4 mm. For the Ring antenna, within the frequency range of interest, i.e., 3.75 -4.25 GHz, path loss is smallest, approximately 60 dB, as the capsule is located on the middle of SI.…”
Section: A On-body Antenna Locationmentioning
confidence: 93%
“…Especially in the abdomen area, tilt angles may vary significantly depending on the shape of the abdomen area. Furthermore, as presented in [8], the impact of antenna and body distance can have significant impact on the channel characteristics. Simulation based studies of [8] show that only 2mm difference can cause even 8 dB difference to the level of the main peaks.…”
Section: A Antenna Location 1 Side-by-side Casementioning
confidence: 99%
“…Furthermore, as presented in [8], the impact of antenna and body distance can have significant impact on the channel characteristics. Simulation based studies of [8] show that only 2mm difference can cause even 8 dB difference to the level of the main peaks. Hence, the thickness of the cloth may affect significantly on the measurement results.…”
Section: A Antenna Location 1 Side-by-side Casementioning
confidence: 99%
“…As these antennas operate in the proximity of lossy body tissues, their performance is greatly affected by the user. Based on measurements [8]- [10] and Electromagnetic (EM) simulations [11]- [13], the antenna efficiency is reported to be strongly impacted by the body for separations below 8 mm, while this impact is negligible when the antenna is more than 15 mm away from the body. Moreover, different body types [10], [14] and on-body antenna locations [15]- [19] have a clear impact on the radiation characteristics.…”
Section: Introductionmentioning
confidence: 99%